2012
DOI: 10.1128/cvi.05460-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Different Sources of Pertussis Toxin (PT) as Coating Antigens in IgG Anti-PT Enzyme-Linked Immunosorbent Assays

Abstract: In an effort to improve the reliability and reproducibility of serological assays for Bordetella pertussis, a collaborative study was conducted to compare four different sources of pertussis toxin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Pertussis IgG enzyme-linked immunosorbent assays (ELISAs) were used to quantify the concentration of antibodies to PT, FHA, PRN, and FIM, expressed in ELISA Units per milliliter (EU/mL). (10) The lower limit of quantitation (LLOQ) was 3 EU/mL for FHA and 4 EU/mL for PT, PRN and FIM. Anti-tetanus toxoid antibodies were measured by IgG ELISA using the World Health Organization (WHO) International Standard for Tetanus Immunoglobulin, Human, Lot TE3.…”
Section: Methodsmentioning
confidence: 97%
“…Pertussis IgG enzyme-linked immunosorbent assays (ELISAs) were used to quantify the concentration of antibodies to PT, FHA, PRN, and FIM, expressed in ELISA Units per milliliter (EU/mL). (10) The lower limit of quantitation (LLOQ) was 3 EU/mL for FHA and 4 EU/mL for PT, PRN and FIM. Anti-tetanus toxoid antibodies were measured by IgG ELISA using the World Health Organization (WHO) International Standard for Tetanus Immunoglobulin, Human, Lot TE3.…”
Section: Methodsmentioning
confidence: 97%
“…Three of four participants used the same reference serum (the CBER standard or the equivalent WHO reference serum). Among those was the only ELISA (from the CDC) in which one dilution of test samples was used (233). The authors concluded that using the same reference serum may be the dominant important parameter for comparability.…”
Section: Serodiagnosis Of Pertussismentioning
confidence: 99%
“…These results led to a recently completed study to compare the effects of four sources of PT antigen preparations on four different ELISA methods. Results demonstrated that if the preparations are highly purified and well qualified and the ELISAs are calibrated to a reference standard and well validated, these different PT sources could be interchangeably used (13).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the anti-PT IgG ELISA have been previously described (13,19). The diagnostic ELISA is a single-point, single 1:100 dilution assay that contains six ready-to-use standards and three ready-to-use controls (negative, intermediate, and positive).…”
Section: Methodsmentioning
confidence: 99%